Design of peak voltage absorption device of frequency-conversion speed-regulation for winch - LYU Fengxin; DU Peng; SU Liangcheng; YU Yuesen (Gong-kuang zidonghua, 2015)
In order to reduce influence of peak voltage of motor terminal pulse on the ground insulation of motor and ensure safe and stable operation of frequency-conversion winch, a peak voltage absorption device of frequency-conversion speed-regulation for winch was designed based on the principle of uniform transmission line model and absorption circuit. The device adopts principle of capacitor charging and discharging, and can effectively reduce peak voltage of motor terminal, prevent the motor insulation breakdown. The test results show that the device reduces output voltage change rate of inverter, reduces instantaneous peak of motor terminal, the peak is reduced from 2 820 V to 2 330 V, so the output peak voltage is controlled effectively.